Species and river specific effects of river fragmentation on European anadromous fish species. (26th November 2018) - van Puijenbroek, Peter J.T.M.; Buijse, Anthonie D.; Kraak, Michiel H.S.; Verdonschot, Piet F.M.
Abstract: Fragmentation is one of the major threats to riverine ecosystems and this is most explicitly expressed by the decline in numbers of migratory fish species. Yet each species has different migration requirements and their natural distribution can include several catchments with multiple dams. Hence, to prioritize candidate rivers for improving accessibility, differences between species and between catchments have to be taken into account. The aim of this study was therefore to analyse the species and river specific effects of river fragmentation on migratory fish on a European scale. The effect of river damming on migratory fish was quantified for all 16 European long‐ and mid‐distance anadromous species and for 33 large European rivers. The historical distribution was compared with the current upstream accessibility of the main river and the current distribution and population status of each species. The observed effects of reduced connectivity were further quantified using the Dendritic Connectivity Index for species and the Fragmentation Index for rivers. Our results showed that only very few rivers are still unaffected by dams in the main stem and that the few remaining viable migratory fish populations in Europe occur in these accessible rivers. Barriers were prioritized for making passable based on the potential accessibility gain and the number of benefitting species, showing that the main stems of the rivers Shannon and Nemunas are the best candidates. It was concluded that evaluating species and river specific effects of fragmentation strongly aids in prioritizing rivers for improving upstream accessibility.